Eugenic politics and reproductive rights. A view from (feminist) bioethics of/from functional diversity - Arnau Ripollés, M.ª Soledad (Filanderas, 2017)
The work that is presented gives a different perspective on the social and public health policies that mark the normative horizon of what is social welfare and human relations in bioethical issues.Thus, if we seek human enhancement and would like to understand it as a right, we may be confronted with the human right to be different. Biotechnological and scientific advances open up possibilities and challenges that can go beyond what we could interpret as legitimate. Today, we can create human beings not only according to our ethics, but also according to our whims. Bioethical issues as delicate as eugenic abortion for diversity reasons or forced sterilization as a contraceptive practice for people who are considered different are confronted with the principle of bioethical autonomy, which mitigates free and informed consent.
Keywords: Bioethics; Eugenic abortion; Forced Sterilization; Functional Diversity; Women; Reproductive Rights